Effects of a heat-stable yeast product in pelleted diets for weanling pigs - C A Maloney; Robert H Hines; H Cao; J S Park; Joe D Hancock; Carla S Nemecek (Kansas Agricultural Experiment Station Research Reports, 1998)
The results from two experiments showed that a heat-stable yeast product survived well in diets that were steam conditioned at 158 to 176Â°F and pelletized. Also, inclusion of .2% yeast product resulted in a greater rate of gain and a trend for improved feed efficiency in weanling pigs.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Weanling pigs; Nursery; Yeast